(untitled) (Research, Society and Development, 2023)
This study aims to perform an integrative literature review to understand the causal relationship between neurological disorders and Covid-19 and to point out new updates on the subject. The world experienced the pandemic of coronavirus disease 2019, a severe acute respiratory syndrome caused by the coronavirus SARS-CoV-2, having as one of the most frequent pathological consequences neurological disorders. Damage to the central nervous system (CNS) related to infection can occur due to multiple reasons, including: Damage by direct viral invasion there are neurons; Decreased oxygen levels due to hypoxia; Formation of microthrombi with a persistent inflammatory state that induces cerebrovascular complications. Direct viral invasion leads to adverse effects on neurons in several aspects, such as cell morphology, electrophysiology, subcellular structures, and cell death. Hypoxemia has the ability to disturb the integrity of the blood brain barrier, allowing the infiltration of peripheral immune cells and protein leakage, which promotes CNS dysfunction. To date, epidemiological studies indicate that a high pathological relationship between Covid-19 and neurological diseases. Accumulated evidence indicates that patients who developed Covid-19 may present with long-term apparent neurological symptoms, such as headache, altered mental status, anosmia, and myalgia. The harmful relationship between SARS-CoV-2 infection and neurological diseases is notorious, but new searches to better understand its etiology are crucial.